Play Therapy “Beat The Clock” (Mengalahkan Waktu)” untuk Meningkatkan Atensi Pada Anak Dengan Masalah Innatention - Difiana Yulilla; Rudi Cahyono (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
Children with attention deficit symptom are generally difficult to have focus and centering their attention on long period of time, especially on completing school assignments process. Children with attention-centered symptom are easier to be distracted with many things around whether it is sounds, lights and noises. They also easily nodded and hardly focus on the assignment given. Therefore, there is an intervention to improve children attention and concentration. One of the techniques is play therapy called